1959
DOI: 10.1111/j.1744-7348.1959.tb07277.x
|View full text |Cite
|
Sign up to set email alerts
|

HOST FINDING BY APHIDS IN THE FIELD: APHIS FABAE SCOP. (GYNOPARAE) AND BREVICORYNE BRASSICAE L.; WITH A RE‐APPRAISAL OF THE ROLE OF HOST‐FINDING BEHAVIOUR IN VIRUS SPREAD

Abstract: Aphis fabae gynoparae occurred in the same large proportion in simultaneous collections of all aphids alighting and probing on, and taking off from, a host plant (spindle) and a non‐host (peach), and behaved similarly when approaching and leaving them in the same conditions. Most alighters took off again from leaves of both kinds within a few minutes, staying longer and probing more times on the host. In atmospheric conditions favouring local ‘hovering’ instead of dispersal, flying and alighting aphids became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(29 citation statements)
references
References 30 publications
2
26
0
1
Order By: Relevance
“…The increase in cereal aphid numbers per tiller on oats caused by mixed cropping was reported and discussed elsewhere, as well as the slower development of the incidence to mean ratio of R. padi in the mixtures (Helenius 1989 (1983) concluded that dense monocrops are likely to be less severely damaged than sparse monocrops, but that undersowing or intercropping could bring about a reduction in incidence and virus spread. Taking the dispersive host-finding behaviour of colonizers into account (Kennedy et al 1959), these results support the hypothesis, presented elsewhere in the case of R. padi (Helenius 1989), that intercropping interferes with secondary dispersal after alighting on the crop, primarily via the increased distance between individual host plants. This mechanism would have the greatest effect in replacement intercrops, where the host density is well below the normal density used in monocrops.…”
Section: Pest Incidencesupporting
confidence: 89%
“…The increase in cereal aphid numbers per tiller on oats caused by mixed cropping was reported and discussed elsewhere, as well as the slower development of the incidence to mean ratio of R. padi in the mixtures (Helenius 1989 (1983) concluded that dense monocrops are likely to be less severely damaged than sparse monocrops, but that undersowing or intercropping could bring about a reduction in incidence and virus spread. Taking the dispersive host-finding behaviour of colonizers into account (Kennedy et al 1959), these results support the hypothesis, presented elsewhere in the case of R. padi (Helenius 1989), that intercropping interferes with secondary dispersal after alighting on the crop, primarily via the increased distance between individual host plants. This mechanism would have the greatest effect in replacement intercrops, where the host density is well below the normal density used in monocrops.…”
Section: Pest Incidencesupporting
confidence: 89%
“…Gynoparae could therefore be considered as exhibiting a true migratory (Kennedy, 1985) flight followed by a disinhibition (or recurrence) of targeted flight. These findings indicate that alighting field-gynoparae of A.fabae, observed by Kennedy et al (1959b), had undergone a migratory flight. However, the majority of alighters were still not ready to settle even on a suitable winter host plant.…”
Section: Discussionmentioning
confidence: 83%
“…Similar Phenology and bionomics of cowpea aphid studies with other aphid species on different crop plants have also been reported (Kennedy et al, 1959(Kennedy et al, ,1961Turl, 1980;Dixon, 1985Dixon, ,1990Deguine et al, 1994;Bommarco and Ekbom, 1995). However, studies of dispersion of A. craccivora on cowpeas, and the resulting effects on crop performance have not been well-studied, although understanding such aspects of aphid-crop interactions is crucial for predicting cowpea aphid infestations, the potential impact on crop production and thus, the timely institution of effective pest management programmes.…”
Section: Introductionmentioning
confidence: 99%